Stomach content analysis of Helostoma temmincki from swamp in the Bencah Kelubi Village, Tapung Kiri Sub-Regency, Kampar Regency, Riau Province - Anggraini, Rini; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Helostoma temmincki is a type of fish that inhabit swamp area in Riau. A study aims to understand the stomach content and its relation with size, sex and level of maturity of that fish has been conducted on February to May 2015. Fish samples were captured using gill nets, fish trap and line fishing. Stomach content of the fish was analyzed and it was used as a basis to calculate the Preponderance Index (PI).Total, there were 104 fishes captured, but 27 of them had empty stomach and could not be used for stomach content analysis. The number of fish analysed was 77. Parameters measured were Index of Preponderance (IP), type of food, total length, sex and gonad maturity level. Results shown that the main food of the fish is Bacillariophyceae (45,32%). The small fishes (61-86 mm TL) consume phytoplankton, while the big fish (90-165 mm TL) consume phytoplankton and zooplankton. The male and female’s stomach content was almost the same. Fish with relatively low maturity level eat mainly on phytoplankton, while mature fish consume phytoplankton and zooplankton. Based on data obtained, it can be concluded that the food of H. temmincki was various, and it is related to body size and gonad maturity level.Keyword: Helostoma temmincki, Swamp, Stomach Content Analysis, Index of Preponderance